A Study of the Role & effectiveness of Celebrities in Advertisements - Chavda, Virendra (Indian Journal of Marketing, 2012)
A celebrity's popularity in the masses turns out to be an important criteria in selling a particular product. It is more the trust and love for the celebrity than the quality or durability of a product to be sold. The celebrity endorsement influences the minds of the consumers. Consumers perceive the brand as having superior quality because it has been endorsed by a credible source; this makes endorsement as one of the indictors of quality for any brand. Thus, it is important to study the role of celebrities and their effectiveness in advertisements. This paper aims to ascertain the role of celebrities & measuring the celebrities' effectiveness for aspects such as image creation, attracting audience, surviving competition, overshadowing the product, etc.